Re-regulation of commodity derivative markets: Critical assessment of current reform proposals in the EU and the US - Cornelia Staritz; Karin Küblböck (Austrian Foundation for Development Research (ÖFSE), 2013)
In the context of recent commodity price hikes, a political consensus has emerged on regulatory measures to reduce excessive speculation in commodity derivative markets. This paper gives an overview of current reform proposals of commodity derivate market regulation at the international (G20), US and EU level and assesses their scope and limitations. For such an assessment, the primary functions of commodity derivative markets for the real economy, i.e. price discovery and price risk hedging for commercial traders have to be taken as a benchmark. The paper concludes that important regulatory initiatives have been under way with a focus on improving transparency, regulating over the counter trade, installing position limits and strengthening regulatory authorities. However, there are important limitations, in particular in the form of broad exemptions (e.g. concerning position limits and commercial traders). Regulations that would more substantially reduce the dominance of financial investors and ensure the dominance of fundamentally based trading strategies have only marginally been addressed, such as restrictions on certain trading strategies (e.g. indexbased investments, technical/algorithmic trading, high frequency trading) and price stabilization mechanisms such as a multitier financial transaction tax. A prerequisite for effective regulation is a pro-active, flexible and dynamic approach that reflects on the risks of failure and adapts regulations if necessary given the changing dynamics and complexities of markets. Further, effective regulation has to take into account the multiple and interrelated roles of financial and large commercial traders being increasingly involved in speculative derivative and physical commodity trading.
Keywords: 330; Rohstoffderivat; Finanzmarktregulierung; Reform; Vergleich; EU-Staaten; USA